Methods for studying video games and religion - Šisler, Vít; Radde-Antweiler, Kerstin; Zeiler, Xenia (Routledge studies in religion and digital culture, 2018)
Introduction : level up : methods for studying video games and religion / Xenia Zeiler -- Critical discourse analysis : studying religion and hegemony in video games / Kathrin Trattner -- Gaming elicitation in episodic interviews : let's play baptism / Kerstin Radde-Antweiler -- An ethnographic method for the study of religion in video game environments / Gregory Price Grieve -- Surreal impersonation / William Sims Bainbridge -- Design-based research : mobile gaming for learning Jewish history, tikkun olam, and civics / Owen Gottlieb -- Phenomenological hermeneutics as a bridge between video games and religio-aesthetics / Mikhail Fiadotau -- Empirical triangulation : applying multiple methods to explor e religion and myth through video games / Enrico Gandolfi -- Petri net modeling : analyzing rule-based representations of religion in video games / Vít Sisler -- Qualitative in-depth interviews : studying religious meaning-making in MMOs / Stef Aupers, Julian Schaap and Lars de Wildt -- Normalized social distance : quantitative analysis of religion-centered gaming pages on social networks / Josef Slerka and Vít Sisler -- Coding comments on gaming videos : YouTube Let's Plays, Asian games, and Buddhist and Hindu religions / Xenia Zeiler -- How to study religion and video gaming : a critical discussion / Kerstin Radde-Antweiler